2020
DOI: 10.3390/antiox10010043
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into the Regulation of Lipoxygenase-Driven Lipid Peroxidation Events in Human Spermatozoa and Their Impact on Male Fertility

Abstract: A prevalent cause of sperm dysfunction in male infertility patients is the overproduction of reactive oxygen species, an attendant increase in lipid peroxidation and the production of cytotoxic reactive carbonyl species such as 4-hydroxynonenal. Our previous studies have implicated arachidonate 15-lipoxygenase (ALOX15) in the production of 4-hydroxynonenal in developing germ cells. Here, we have aimed to develop a further mechanistic understanding of the lipoxygenase-lipid peroxidation pathway in human spermat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In accounting for this phenomenon, it is perhaps notable that each of these functional parameters are acutely sensitive to elevated levels of reactive oxygen species, the excessive production of which is a common etiology in the spermatozoa of infertile males (74). Indeed, work in our own laboratory has shown that molecular chaperone proteins (i.e., heat shock protein A2; HSPA2), which coordinate capacitation-associated membrane remodeling, are highly vulnerable to adduction by reactive lipid aldehydes [including 4-hydroxynonenal (4HNE)] formed as a consequence of oxidative-stress induced membrane lipid peroxidation (75)(76)(77). Such adductions disrupt HSPA2-client protein interactions and consequently limit the surface presentation of ZP receptors in capacitated spermatozoa (63).…”
Section: Sperm-zona Pellucida Bindingmentioning
confidence: 99%
“…In accounting for this phenomenon, it is perhaps notable that each of these functional parameters are acutely sensitive to elevated levels of reactive oxygen species, the excessive production of which is a common etiology in the spermatozoa of infertile males (74). Indeed, work in our own laboratory has shown that molecular chaperone proteins (i.e., heat shock protein A2; HSPA2), which coordinate capacitation-associated membrane remodeling, are highly vulnerable to adduction by reactive lipid aldehydes [including 4-hydroxynonenal (4HNE)] formed as a consequence of oxidative-stress induced membrane lipid peroxidation (75)(76)(77). Such adductions disrupt HSPA2-client protein interactions and consequently limit the surface presentation of ZP receptors in capacitated spermatozoa (63).…”
Section: Sperm-zona Pellucida Bindingmentioning
confidence: 99%
“…Low levels of O 2 •− , H 2 O 2 and peroxynitrite, modulate cellular functions, but when they are produced in excess cause nitro-oxidative damage ( Quijano et al, 2007 ). Nitro-oxidative stress is associated with altered semen parameters and abnormalities in the process of fertilization and pregnancy ( Twigg et al, 1998 ; Agarwal et al, 2014a ; Walters et al, 2020 ). In addition, mitochondrial dysfunction is associated with an increase in nitro-oxidative damage in sperm and a decrease in sperm motility ( Cassina et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%